2018
DOI: 10.1111/bjdp.12261
|View full text |Cite
|
Sign up to set email alerts
|

The role of intelligence in decision‐making in early adolescence

Abstract: This study investigated the role of intelligence and its development across childhood in decision-making in adolescence (age 11 years). The sample was 12,514 children from the UK's Millennium Cohort Study, followed at ages 3, 5, 7, and 11 years. Decision-making (risk-taking, quality of decision-making, risk adjustment, deliberation time, and delay aversion) was measured with the Cambridge Gambling Task. Even after adjustment for confounding, intelligence was positively associated with risk adjustment and quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 24 publications
0
10
0
2
Order By: Relevance
“…Finally, older youth have been shown to rely more heavily on base rate information than on individuating information (Kokis et al, 2002;Toplak et al, 2014), but other studies have shown mixed findings, depending on the domain under study (Jacobs & Potenza, 1991;Klaczynski, 2001b). Developmental differences on cognitive bias tasks have been primarily studied cross-sectionally, with relatively fewer longitudinal studies of judgment and decision making in developmental samples (Almy, Kuskowski, Malone, Myers, & Luciana, 2018;Flouri, Moulton, & Ploubidis, 2019). We predicted growth in RCB performance in our longitudinal developmental study.…”
Section: Rcb and Developmentmentioning
confidence: 82%
“…Finally, older youth have been shown to rely more heavily on base rate information than on individuating information (Kokis et al, 2002;Toplak et al, 2014), but other studies have shown mixed findings, depending on the domain under study (Jacobs & Potenza, 1991;Klaczynski, 2001b). Developmental differences on cognitive bias tasks have been primarily studied cross-sectionally, with relatively fewer longitudinal studies of judgment and decision making in developmental samples (Almy, Kuskowski, Malone, Myers, & Luciana, 2018;Flouri, Moulton, & Ploubidis, 2019). We predicted growth in RCB performance in our longitudinal developmental study.…”
Section: Rcb and Developmentmentioning
confidence: 82%
“…For example, Li et al (2017) found that intellectually gifted children have better IGT performance than intellectually average children. A recent study of Flouri et al (2019) have found that children's IQ was substantively related to the quality of decision-making measured by another gambling task-Cambridge gambling task. Furthermore, researchers proposed that affective decisionmaking measured by the IGT demands inductive reasoning (important aspect of IQ) from participants through the trialand-error process of IGT (Busemeyer and Townsend, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…For example, gifted children outperformed their average peers in regards of decision-making strategies and speed, which suggests that IQ can predict the affective decision-making ability of children and early adolescents ( Li et al, 2017 ). Another study ( Flouri et al, 2019 ) with over 12,000 participants found that intelligence was substantively associated with the risk adjustment and quality of decision-making measured by the performance of Cambridge Gambling Task in early adolescence (aged 11). By comparing the different findings of existing papers in IGT, we believe that the inconsistent results are due to different choice of indices.…”
Section: Introductionmentioning
confidence: 99%
“…Интеллектуальные способности изучаются отечественными психологами в связи с одаренностью человека (Валуева и др., 2015; Григорьев и др., 2017), продуктивностью в разных видах и типах деятельности (Денисенкова, Выроцкова, 2015;Morosanova et al, 2015;Белова, Смирнова, 2015). В зарубежных исследованиях можно выделить две группы исследований интеллектуальных способностей, связанных с изучением их роли в академических достижениях (Freedberg et al, 2019;Mammadov et al, 2018;Tao, Jiannong, 2018) и развитии личности в разные возрастные периоды (Flouri et al, 2019;Kätlin, René, 2019).…”
Section: предмет исследованийunclassified